1976
DOI: 10.1007/bf00426833
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the action of lysergic acid diethylamide and apomorphine on the copulatory response in the female rat

Abstract: The effects of lysergic acid diethylamide (LSD) and apomorphine were compared using female copulatory behavior (lordosis response), in ovariectomized estrogen + progesterone-treated rats. Both serotonin and dopamine are implicated in the inhibition of this behavior. Each compound inhibited lordosis behavior dose dependently and with a similar time-course. Pimozide (0.1; 0.5 mg/kg) blocked the apomorphine (0.2 mg/kg)-induced decrease of lordosis response, while only a certain abbreviation of the LSD (0.10 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…The choice for apomorphine, ±8‐OH‐DPAT, and paroxetine were based on studies described in the literature. Several studies showed the inhibiting effect of apomorphine on female sexual behavior, by a decrease in proceptive behavior [23], lordosis [24–26], and incentive motivation [23] after administration of dopamine‐increasing agents. Also the inhibiting effect of ±8‐OH‐DPAT on lordosis behavior [27–29] was described in the literature in the past.…”
Section: Introductionmentioning
confidence: 99%
“…The choice for apomorphine, ±8‐OH‐DPAT, and paroxetine were based on studies described in the literature. Several studies showed the inhibiting effect of apomorphine on female sexual behavior, by a decrease in proceptive behavior [23], lordosis [24–26], and incentive motivation [23] after administration of dopamine‐increasing agents. Also the inhibiting effect of ±8‐OH‐DPAT on lordosis behavior [27–29] was described in the literature in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have claimed that LSD also influcences dopaminergic receptors ( Grabowska et aL, 1974;Pieri et al, 1974;Da Prada et aL, 1975). However, Eliasson and Meyerson (1976) demonstrated that the predominant action of LSD on the female copulatory response is not mediated by increased dopamine activity, as the selective dopamine antagonist pimozide did not prevent the LSD-induced decrease in L.R. Since tritiated LSD binds to 5-HT1 and 5-HT 2 receptors to the same extent (Peroutka and Snyder, 1979), we found the drug useful in the present study, where the population of 5-HT receptors involved in the lordotic behavior was investigated.…”
Section: Discussionmentioning
confidence: 95%
“…Compounds that reduce the 5-HT level in the brain facilitate lordosis, and drugs that increase brain 5-HT inhibit it (Meyerson et al, 1973;Meyerson et aL, 1974;Everitt et aL, 1975;Meyerson and Eliasson, 1977;Meyerson and Malmnds, 1978;Sietnieks and Meyerson, 1980, 1983). In addition, a variety of facilitatory and inhibitory actions appear to be exerted by other neurotransmitters such as dopamine (Everitt et aL, 1975;Eliasson and Meyerson, 1976;Foreman and Moss, 1979), norepinephrine (Foreman and Moss, 1978;Glaude, 1979) andacetylcholine (Lindstr6m, 1973;Clemens et aL, 1981).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…48,49 On the other Dopamine and sexual function F Giuliano and J Allard hand, apomorphine was found to be able to increase the lordotic response of ovariectomised rats treated with oestrogen and progesterone when given systemically. 50 Stimulation of D 2 receptors by either LY171555 or LY163502 was also found to increase the lordotic response of low receptive ovariectomised oestrogen treated rats.…”
Section: Involvement Of Da In Female Rat Sexual Motivationmentioning
confidence: 99%